Campur Kode dalam Film Arab Alrabawi School For Girls Karya Tima Shomali: Bentuk dan Faktor yang Mempengaruhi (Kajian Sosiolinguistik) - Sri Wahyuni Lestari; Muassomah Muassomah; Penny Respati Yurisa (Institut Agama Islam Negeri Metro, 2023)
The film Alrawabi School For Girls is an Arabic film with the theme of the lives of multilingual teenagers. This film, directed by Tima Shomali and Shirin Kamal, tells of a girl who is bullied taking revenge on her bully, only to realize that no one is completely bad, and no one is completely good, including herself. This research is an analysis of mixing English code into Arabic in the film Alrawabi School For Girls. Not only describing the findings related to code mixing in this film, this research also reveals the factors that cause code mixing. This study uses a qualitative approach Moleong mode, with a type of literature study. Data was collected through observing and noting techniques on data sourced from films. Furthermore, the data was analyzed through three stages, organizing, sorting, describing, and drawing conclusions. This study found a type of external code mixing, namely speakers mixing two languages that are not related both geographically and genealogically. Found data in the form of code mixing as much as 20 data. With each type, such as code mixing at the word level with 6 data, code mixing at the phrase level with 11 data, and code mixing at the clause level with 3 data. Factors that cause code mixing in the film Alrawabi School For Girls include (a) the participants have the same mother tongue background (b) the speaker's desire to get the right expression (c) the habits and relaxedness of the speech act participants in communicating.